Nonlinear rotordynamics of a MDOF rotor–stator contact system subjected to frictional and gravitational effects - Elijah Chipato (Mechanical Systems and Signal Processing, 2021)
Rotating machines are intrinsically susceptible to expensive and high-risk faults such as rotor–stator rub. During a rub event normal and tangential forces are generated by the contact and friction that cause wear at the contacting interfaces. In the present work, such forces are computed by assuming linear elastic contact and Coulomb friction at multiple interface locations. A finite element shaft-line model of a horizontally mounted rotor is used to demonstrate the approach and the model is reduced for computational efficiency. The modal assurance criterion is used to identify the linear modes that contribute to a given solution. It is observed that bouncing solutions exist with rotor–stator contact in complex machines that can be viewed as internal resonances involving a small number of modes. The responses can become complex because different modes can combine to give the internal resonance (and hence a larger range of frequency ratios) and because of asymmetries, such as gravity. One design goal is to avoid any contact in the system and the analysis in this paper identifies the conditions for internal resonance that should be avoided in a real machine. The complicated dynamics shown here reveal some of the distinct features of contacting solutions and could also be used in condition monitoring to characterise faults.